STRATEGI IMPLEMENTASI SISTEM INFORMASI MANAJEMEN "KEMBANG DAMAN" DALAM MENINGKATKAN MUTU PELAYANAN KANTOR KEMENAG KABUPATEN JOMBANG - Jauhari, Rafi (Ulul Amri: Jurnal Manajemen Pendidikan Islam, 2024)
In the era of digitalization, it is important for every Office of the Ministry of Religious Affairs to utilize information technology to improve the efficiency and quality of services, including madrasah education, Islamic boarding schools, Islamic community development, waqf and zakat, staffing, and hajj and umrah. With an area of 1,109.63 km² and a large population, the Jombang District Office of the Ministry of Religious Affairs created a management information system called “Kembang Daman” to facilitate community access, especially in peripheral areas. Despite facing challenges such as data management and security, skilled human resources, and appropriate strategies, this study aims to provide guidance for the Ministry of Religious Affairs of Jombang and similar entities in utilizing information technology to improve the quality of public services in the digital era, as well as providing an understanding of the role of technology in public service delivery and its impact on society. This study examines and understands (1) the strategy of the Management Information System “Kembang Daman” in improving the quality of service of the Office of the Ministry of Religious Affairs of Jombang Regency, (2) the implementation of the system, and (3) the results of its use in efforts to improve service quality. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. Data were processed through a process of collection, condensation, presentation, and conclusion drawing, with data credibility tested through triangulation procedures of sources, methods, and member checking. The results showed that the implementation strategy of the Management Information System “Kembang Daman” at the Office of the Ministry of Religious Affairs of Jombang Regency includes formulation, implementation, and control. At the formulation stage, the system was included in the 2020-2024 Strategic Plan (Renstra) with a division of tasks between Pre-Comm, PTSP, and Public Relations. The implementation stage involves system integration, change management, and the provision of innovative features such as real-time online services and application status monitoring, as well as socialization through social media. In the control phase, monitoring is done through review and barcode assessment features, as well as continuous evaluation to improve the system. Overall, the implementation of “Kembang Daman” improved the efficiency, accuracy, transparency, and responsiveness of services at the Ministry of Religious Affairs in Jombang, and increased public satisfaction with the services provided.